The Deconstruction Of Character Education - Chaer, Moh Toriqul (IJTB (International Journal of Technology And Business), 2017)
This study seeks to bring the management of education not only in normative; simply stating and describing, but transformed in the form of performative actions; that is actual and concrete action. One of them is the effort presents the idea of cultural-based character education. The dynamics of the times will keep rolling including education, then the necessary efforts to deconstruct an old-fashioned texts that had evolved in the world of education. This effort is not an sich demanding professional attitude in the management of education, but also how to build a dialectic between the text being taught with the existing reality. Character education theme can be used as an alternative for the education of this nation, what is the purpose of this character-based learning, idea is able to advocate inequality and discrimination social-cultural happening in society. Understanding and contextual understanding of how began a good character education on the learners obviously have an impact on the understanding of the behaviour, acts that can be accounted for. Expected in the end of education can advocate for learners in a mensikapi culture that concussion occurred in the community with arif and wise with the emphasis on local wisdom values (local wishdom) an egalitarian and humanistic.